2019
DOI: 10.14814/phy2.14006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular characterization of human epicardial adipose tissue: highly expressed PAPP-A regulates insulin-like growth factor I signaling in human cardiomyocytes

Abstract: Little is known about the cellular biology of fat surrounding the human heart. In this study, we obtained paired samples of epicardial fat, the visceral fat depot attached to the heart, and subcutaneous skin fat from patients undergoing open heart surgery to test the hypothesis that human epicardial fat cells differentially express bioactive molecules that have the potential to affect cardiac function. First, we characterized the free fatty acids (FFAs), adipocytokines, and growth factors secreted by isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Insulin is well known to play a critical role in triggering and maintaining preadipocyte differentiation. Insulin binds to its receptor and then triggers the phosphorylation of IRS, which, in turn, recruits and sequentially activates PI-3K and AKT [14,15], which plays important roles in adipose biology [37,38]. Although insulin is known to stimulate adipocyte differentiation dose-dependently at the early stage of differentiation [39], Konneker et al recently reported that high concentration of insulin (>3.4 μM) inhibits lipid storage in the late phase of human primary preadipocytes differentiation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is well known to play a critical role in triggering and maintaining preadipocyte differentiation. Insulin binds to its receptor and then triggers the phosphorylation of IRS, which, in turn, recruits and sequentially activates PI-3K and AKT [14,15], which plays important roles in adipose biology [37,38]. Although insulin is known to stimulate adipocyte differentiation dose-dependently at the early stage of differentiation [39], Konneker et al recently reported that high concentration of insulin (>3.4 μM) inhibits lipid storage in the late phase of human primary preadipocytes differentiation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial adipose tissue is a visceral fat deposit accumulated between the pericardium and the myocardium, sharing many pathophysiological characteristics with other visceral fat depots (21). It may also cause local inflammation and likely has direct effects on coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It may also cause local inflammation and likely has direct effects on coronary atherosclerosis. A recent study by Conover et al has shown that PAPP-A is produced in large amount by preadipocytes from human epicardial fat and regulates IGF-I signaling in cardiomyocytes (21). Thus, the authors hypothesize that bioactive products from epicardial fat are disseminated and interact locally with the coronary arteries and heart through the microcirculation, herby accelerating atherosclerotic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were washed twice with cold PBS and lysed with 150 ul RIPA buffer containing protease and phosphatase inhibitors, as previously described (Conover et al, 2019). Briefly, cells were scraped into microfuge tubes, sonicated, centrifuged and the supernatant transferred to a new tube.…”
Section: Methodsmentioning
confidence: 99%